Integrated Voltage Vector-Based SVPWM for Reliability and Performance Enhancement of Five-Level HANPC Inverters - Halabi, Laith M.; Hakami, Samer Saleh; Lee, Kyo Beum (IEEE Transactions on Industrial Electronics, 2024)
Power converters are designed to operate over a wide range of voltages to meet various industrial demands. Recently, multilevel inverters have been receiving considerable attention owing to their ability to reduce the current ripple and its associated harmonic distortion. However, for applications requiring high voltage/power ratings, large electrolytic capacitors are essential, which are significantly affected by the ripple in the dc-link current. This causes a significant reduction in the lifespan and reliability of the power converter and necessitates expensive diagnosis and maintenance procedures. Therefore, an effective method of integrated voltage vector (VV) based space vector pulse-width modulation is proposed in this article for minimizing the ripple in the dc-link and common-mode voltage of five-level hybrid active neutral-point-clamped (5L-HANPC) inverters. The proposed method uses a unique control algorithm that can smoothly select the required VVs without a noticeable distortion in the output current waveforms. Moreover, the proposed method can be applied without modifying the original topology of the 5L-HANPC inverter or adding complex compensations to the control algorithm. Extensive simulation and experimental results are provided to demonstrate the capability of the proposed approach to reduce the dc-link current ripple over a wide range of modulation indices.
Keywords: Current ripples; Dc-link; DC-link capacitor; Five-level converter; HANPC; Insulatedgate bipolar transistor (IGBTs); Inverter; MOS-FET; MOSFETs; Voltage vectors; Current ripple; dc-link capacitors; five-level converters; hybrid active neutral-point-clamped (HANPC); reliability